2021
DOI: 10.3389/fmicb.2021.656956
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Natural Synergetic Antimicrobial Consortia Against Salmonella enterica on Broiler Chicken Carcasses

Abstract: The currently most utilized antimicrobial agent in poultry processing facilities is peracetic acid, a chemical increasingly recognized as hazardous to human health. We evaluated the efficacy of mixtures of natural antimicrobial compounds, namely reuterin, microcin J25, and lactic acid, for reducing the viability of Salmonella enterica and total aerobes on broiler chicken carcasses. The compounds were compared singly and in combination with water and 0.1% peracetic acid. The minimum inhibitory concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In our previous study, the minimum inhibitory concentration of RJ on S. enterica was determined to be 0.5 mmol/L (reuterin) and 0.008 μmol/L (microcin J25), respectively [ 16 ]. Concentrations of 1, 5, and 10 times the minimum inhibitory concentration of RJ were used in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, the minimum inhibitory concentration of RJ on S. enterica was determined to be 0.5 mmol/L (reuterin) and 0.008 μmol/L (microcin J25), respectively [ 16 ]. Concentrations of 1, 5, and 10 times the minimum inhibitory concentration of RJ were used in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Combinations may make each antimicrobial compound effective at a lower concentration and the emergence of resistant variants less likely [ 14 , 15 ]. In our previous study [ 16 ], compared to using them alone, the combination of reuterin and microcin J25 (RJ) at lower concentration has already been proved to be synergistic for reducing counts of Salmonella enterica on chicken carcasses.…”
Section: Introductionmentioning
confidence: 99%
“…Reuterin was produced by L. reuteri ATCC 53,608 as described previously 14 . An overnight grown culture of L. reuteri in MRS media supplemented with 20 mM glycerol was centrifuged (1500× g , 10 min, 20 °C), and washed with 0.1 M potassium phosphate twice before resuspending them in 300 mM glycerol and incubating anaerobically for 45 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Reuterin is a low molecular weight aldehyde produced by bioconversion of glycerol by the lactic acid bacteria ( Lactobacillus reuteri) . The antimicrobial activity of reuterin was extensively studied 14 17 . We previously demonstrated that up to 20 mg/mL of reuterin could be safely used as a bio-preservative and therapeutic agent 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Humans are mainly infected with S. Typhimurium by eating contaminated food of animal origin ( 6 ). Under such conditions, animal food producers and processors must employ efficient preventive strategies to control Salmonella (including the Typhimurium serotype) throughout the supply chain ( 7 ).…”
Section: Introductionmentioning
confidence: 99%